Assessment of the quality and safety of the drinking water utilized by the residents of Looc, Balete, Batangas - Gonzales, Megielyn P.; Rumbaoa, Rowena Grace O. (2000., 2000)
ABSTRACT People living in rural areas are still the simple mode of living and even their drinking water is still derived from the so called underground reservoir which is considered to be raw water. The study was performed to answer the request of the residents of Barangay Looc which is part of the municiplality of Balete in Batangas because they observed that their drinking water have objectionable taste, color and even odor. Seven water stations were identified as the most frequently used by the residents in the area. Samples from the selected sites were subjected to microbiological examination. The MPN technique was used to assess the presence of microorganisms, which are fecal origin while the Total Plate Count was used to estimate the total count of all viable microorganisms. All of the seven samples gave total counts ranging from 3.05 x 〖10〗^4 CFU/ml of sample to the highest count of 8.3 x 〖10〗^6 CFU/ ml. Among the seven samples assessed in terms of fecal contamination, two pump station were reported to have less than 3 MPN/ 100 ml and both stations were observed to be far from the domestic sewage system. The rest, which are located near the households' sewage system, are said to be positive for coliforms based on the test results. The presence of metals in the water samples was detected using Atomic Absorption Soectrophotometry at the Analytical Services Laboratory of the Institute of Chemistry in UP Diliman. The results revealed that all contained iron precipitates that tend to alter the physical parameters of the groundwater. However, only four of the tested samples exceeded the standard value of the Philippine National Standard which is 1.0 mg/L of total iron. The lead content of all the samples is reported to be below the standard of World Health Organization which is 0.05 mg/L. The results were reported to be respective owners of the pump stations to inform them of the condition of their drinking water.
Thesis (BSFT)-- University of the Philippines Diliman.
Keywords: Drinking water; Rural water supply -- Philippines -- Batangas; Water -- Analysis